Melawan Money Politics dalam Elektoral: Upaya Mereduksi Kejahatan Politik Masuk Gereja - Yonatan Alex Arifianto (Sekolah Tinggi Alkitab Batu, Malang, 2023)
Rampant money politics can be an indicator in society that political education and the importance of maintaining a healthy democracy are being degraded. It cannot be denied that money politics has become a new way to gain leadership positions and also an opportunity for society that is in harmony with the needs and reasonable assumptions that money politics has become the right place for prospective leaders to violate the law and norms of truth. Therefore, the church must have integrity in building a congregation with the character of Christian faith, rejecting all political crimes, including money politics. Using qualitative research methods with a literature study approach, it can be concluded that money politics and its challenges for the church will continue to exist and can lead the church to commit crimes if it does not teach and provide correct political education. With political teaching and education, church members can automatically reduce the evils of money politics in the church. For this reason, the active role of the actualization of Christianity in politics in a holistic and massive manner in the task of educating and directing church members continues to be carried out as part of national and state life which respects the law and of course protects the good name of the church so that it does not fall into political crimes. Keywords: Money Politics, Electoral Affairs, General Elections, Church Politics, reducing crime AbstrakMoney politics yang merajalela dapat menjadi indikator masyarakat bahwa pendidikan politik dan pentingnya menjaga demokrasi yang sehat telah mengalami degradasi. Hal itu tidak dapat dipungkiri bahwa adanya money politics sudah menjadi cara baru untuk melenggang dalam tampuk kepemimpinan dan juga kesempatan bagi masyarakat yang selaras dengan kebutuhan serta anggapan wajar money politics menjadi ajang tepat para bakal calon pemimpin melanggar hukum dan norma kebenaran. Oleh karena itu gereja harus memiliki integritas dalam membangun jemaat berkarakter iman Kristen menolak segala kejahatan agenda politiknya, termasuk money politics. Menggunakan metode penelitian kualitatif dengan pendekatan studi literature maka dapat disimpulkan bahwa money politics dan tantanganya bagi gereja akan terus ada dan dapat membawa gereja dalam tindakan kejahatan bila tidak mengajarkan dan memberikan pendidikan politik yang benar. Dengan adanya pengajaran dan pendidikan politik maka dengan sendirinya warga gereja dapat mereduksi kejahatan money politics dalam gereja. Untuk itu peran aktif dari aktualisasi kekristenan dalam perpolitikan secara holistik dan masif dalam tugas mendidik dan mengarahkan warga gereja terus dilakukan sebagai bagian dari hidup berbangsa dan bernegara yang menghormati undang-undang dan tentunya menjaga nama baik gereja untuk tidak masuk dalam kejahatan politik. Kata Kunci: Politik Uang, Elektoral, Pemilihan Umum, Politik Gereja, mereduksi kejahatan